Pendekatan Berdiferensiasi dalam Pembelajaran Bahasa - Sanulita, Henny (Universitas Tanjungpura, 2023)
Learning Indonesian in the independent learning curriculum is carried out with the implications of learning, thinking, philosophizing, and seeking knowledge. This is in accordance with the concept of differentiated learning. The teacher's task is to create a learning environment that always supports students through education that frees students' thoughts and potential. Without efforts and changes from educators, changes in students are difficult to realize. The researcher conducted a literature review on the application of a differentiated approach in learning Indonesian, with a focus on three different aspects, namely: content, process and results. The purpose of this literature review is to explain how a differentiated approach in teaching Indonesian is applied, the results achieved, and the opportunities offered. The method used in this literature review is the collection of information from scientific research articles for the last five years using the keyword